Reference Region Modeling Approaches for Amphetamine Challenge Studies with [11C]FLB 457 and PET. Issue 4 (April 2015) - Sandiego, Christine M; Gallezot, Jean-Dominique; Lim, Keunpoong; Ropchan, Jim; Lin, Shu-fei; Gao, Hong; Morris, Evan D; Cosgrove, Kelly P
Detecting fluctuations in synaptic dopamine levels in extrastriatal brain regions with [ 11 C]FLB 457 and positron emission tomography (PET) is a valuable tool for studying dopaminergic dysfunction in psychiatric disorders. The evaluation of reference region modeling approaches would eliminate the need to obtain arterial input function data. Our goal was to explore the use of reference region models to estimate amphetamine-induced changes in [ 11 C]FLB 457 dopamine D2/D3 binding. Six healthy tobacco smokers were imaged with [ 11 C]FLB 457 at baseline and at 3 hours after amphetamine (0.4 to 0.5 mg/kg, per os) administration. Simplified reference tissue models, SRTM and SRTM2, were evaluated against the 2-tissue compartmental model (2TC) to estimate [ 11 C]FLB 457 binding in extrastriatal regions of interest (ROIs), using the cerebellum as a reference region. No changes in distribution volume were observed in the cerebellum between scan conditions. SRTM and SRTM2 underestimated binding, compared with 2TC, in ROIs by 26% and 9%, respectively, with consistent bias between the baseline and postamphetamine scans. Postamphetamine, [ 11 C]FLB 457 binding significantly decreased across several brain regions as measured with SRTM and SRTM2; no significant change was detected with 2TC. These data support the sensitivity of [ 11 C]FLB 457 for measuring amphetamine-induced dopamine release in extrastriatal regions with SRTM and SRTM2.